2020
DOI: 10.3390/ijerph17072575
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Tooth Extractions and Related Risk Factors in Adult Patients: A Cohort Study

Abstract: Background: The aim of this study was to evaluate oral status, the reasons for tooth extractions and related risk factors in adult patients attending a hospital dental practice. Methods: 120 consecutive patients ranging from 23 to 91 years in age (mean age of 63.3 ± 15.8) having a total of 554 teeth extracted were included. Surveys about general health status were conducted and potential risk factors such as smoking, diabetes and age were investigated. Results: a total of 1795 teeth were missing after extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
55
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 36 publications
6
55
0
3
Order By: Relevance
“…Dental caries, however, was the main cause of tooth extraction in patients aged 50 years and younger, a similar finding was reported by several studies and attributed it to irregular dental visits, fail to comply with oral hygiene instructions, and high sugar intake. 8 , 10 , 17 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dental caries, however, was the main cause of tooth extraction in patients aged 50 years and younger, a similar finding was reported by several studies and attributed it to irregular dental visits, fail to comply with oral hygiene instructions, and high sugar intake. 8 , 10 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…Passarelli et al have reported that diabetes and smoking habits have a direct association with tooth loss. 8 On the other hand, Kawahara et al have reported that there was no clear correlation between systemic diseases, such as diabetes, and tooth loss. 15 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lollobrigida M [ 18 ] shows that such approaches often determine some implant surface alterations with detrimental effects on re-osseointegration and as air powder abrasion with glycine powder, and 3 W diode laser had the lowest impact on surface physicochemical properties. In order to evaluate oral status, reasons for tooth extractions and related risk factors from the study of Passarelli PC [ 19 ], it has emerged that caries and periodontal disease were the most common causes of extraction in the adult population; therefore, screening strategies might be required for the early interception of caries and periodontal disease and decrease the number of tooth extraction. Knowledge of prevention is also important among teachers because schools are the second houses of children and, from the study of Uzarevic Z [ 20 ], it was found that future primary school teachers have a lack of knowledge for immediate reply to tooth avulsion, leaving poor chances for a successful prognosis of tooth replantation.…”
mentioning
confidence: 99%